2019
DOI: 10.20873/uft.2359365220196especialp48
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem Do Fenômeno De Transferência De Massa Na Hidratação Do Cereal Matinal

Abstract: A crocância do cereal matinal está associada a qualidade do produto e é de suma importância dentre suas características sensoriais. O processo de hidratação o qual ele geralmente sofre antes de ser ingerido, pode ocasionar alterações nesta característica e alguns fatores como, quantidade de fluido disponível, temperatura e tempo de hidratação afetam diretamente esse processo.  O objetivo do trabalho foi utilizar modelos empíricos (Cinético de 1ª Ordem e Exponencial) afim de avaliar os parâmetros de hidratação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Evaluating the temperature effect, the increase of the temperature caused an increase in the lipid content, indicating that the mass transfer is greater with the increase in temperature. Such behavior is explained by [18] who evaluated the hydration kinetics of breakfast cereals with skimmed milk and without lactose and observed that the mass transfer is greater at higher temperatures, but tends to decrease with increasing water concentration in the cereals, because the system tends to balance itself. Table 4 shows the result of the Scott-Knott test when analyzed the ash content of the cereal.…”
Section: Physical-chemical Characterizationmentioning
confidence: 98%
“…Evaluating the temperature effect, the increase of the temperature caused an increase in the lipid content, indicating that the mass transfer is greater with the increase in temperature. Such behavior is explained by [18] who evaluated the hydration kinetics of breakfast cereals with skimmed milk and without lactose and observed that the mass transfer is greater at higher temperatures, but tends to decrease with increasing water concentration in the cereals, because the system tends to balance itself. Table 4 shows the result of the Scott-Knott test when analyzed the ash content of the cereal.…”
Section: Physical-chemical Characterizationmentioning
confidence: 98%